Technological development and production of health supplies: challenges for the Unified Health System (SUS) (Bioscience Journal, 2018)
This study discusses the Brazilian model of incentives for the domestic development and production of supplies for public health, considering initiatives implemented from 2003 to 2016. This paper was prepared based on a qualitative bibliographic study, considering authors in the fields of health sciences, public health and public policy, reports by the World Health Organization (WHO), the Organization for Economic CooperationÂ andÂ Development (OECD), Inter-American Development Bank (IDB) and the World Trade Organization (WTO), and official documents available from the Brazilian Federal Government. The paper focuses on the social dimension of health, considering a specific time period in the literature, from 2003 to 2016 and, finally, the new Regulatory Framework for Science, Technology, and Innovation approved in 2016. Various government initiatives were identified in the field of technological development and production to meet the objectives of the SUS according to the literature analysis. Brazil has been substantially increasing investment in Research and Development (R&D) during the last decade, though it lags European and OECD counterparts. Brazilian investment in R&D increased from 1.01% of gross domestic product (GDP) in 2000 to 1.23% in 2012. Despite being the top performer in Latin America (representing 60% of total R&D investment in the region), investment in R&D in Brazil is approximately half the level of European and OECD countries, which invest on average approximately 2% and 2.5% of GDP.